Clinico-epidemiological assessment of Head and Neck Cancer: A retrospective study of 10 years in Eastern India population - Dr. Ruchi Bhuyan, Dr. Sanat Kumar Bhuyan, Sidhant Bhuyan, Akankshya Sahu, Dr. Rajatpanigrahi ,Dr. Abhishek Pati (International Journal of Advanced Science and Technology, 2020)
Head and neck cancer(HNC) is avast term that incorporates different malignancies that includevarious sites of oral cavity, might be maxilla, mandible , lip, floor of the mouth, buccal mucosa,gingiva, soft and hard palate , tongue or pharynx and larynx. Among tumors, oral cancer is one ofthe most common cancer . The current investigation is intended to examine the prevalence of HNCand its relationship with habits, age, sex, and site in the eastern India population.The purpose of thestudy was to report the incidence of head and neck cancer (HNC) and its connotations with habits,age, gender and site in in coastal population of Odisha in eastern India. A retrospective studyconducted from June 2009 to June 2019. A total of 1364 OSCC (oral squamous cell carcinoma)cases were analyzed and the findings were subjected for statistical analysis.Male to female ratio 2:1and the mean age was among 40-59 years. The most common site cancer were buccal mucosa(48.97%) and tongue (16.49%) followed by maxilla (6.94%) and the least common site was lip(1.24%). Tobacco smoking and chewing habit was a common habit among the easternIndianpopulation and the utmost prevalence risk factor for diseases occurrence. Moreover, the smokelessform of tobacco was found to be significantly associated with OSSC, especially in female.The outcomeof this assessment uncover that tobacco utilization is one of the significant reason in the improvementof malignant growth in oral cancer. Thus, spreading awareness about this tobacco-related malignantgrowth among the individuals is essentially important.